2018
DOI: 10.1186/s13071-018-3019-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological niche modeling predicting the potential distribution of Leishmania vectors in the Mediterranean basin: impact of climate change

Abstract: BackgroundDue to climate change, the geographical distribution of sand flies during the last decades has shifted northward from latitudes below 45°N in southern Europe to latitudes just above 50○N. Recent studies show that some phlebotomine sand flies were recorded in several parts of Germany and Belgium. In central Europe, some autochthone leishmaniasis cases are being recorded in regions traditionally regarded as leishmaniasis-free. An important challenge is to predict the geographical distribution of leishm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 48 publications
(35 reference statements)
0
63
0
Order By: Relevance
“…Ecological niche modelling has been widely used in order to identify the probability of sand fly species occurrence (57). To the best of our knowledge, the present study constitutes a first modeling of Sergentomyia species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecological niche modelling has been widely used in order to identify the probability of sand fly species occurrence (57). To the best of our knowledge, the present study constitutes a first modeling of Sergentomyia species.…”
Section: Discussionmentioning
confidence: 99%
“…Precipitation plays an important role in sand flies" life cycle (63). Modeling approach of Chargaff et al (57), found that annual precipitation has a significant role in distribution of Leishmania vector species in Mediterranean basin (57).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these climate variables could also indicate that the distribution of the vector could alter when the climate changes [36,55,73]. For Ethiopia, it is predicted that the temperature will rise, and rainfall will become erratic with ood and drought events likely to increase [74].…”
Section: Discussionmentioning
confidence: 99%
“…Because temperature and precipitation are relevant drivers for the distribution of P. pedifer, bioclimatic variables were derived from 'Climatologies at high resolution for the earth's land surface areas' (CHELSA, https://chelsa-climate.org/bioclim/) with a spatial resolution of 30 arcsec (~ 1 km) [16,31]. A subset of seven out of 19 available bioclimatic variables were considered ecologically relevant to the species and selected, in particular annual averages and extrema (minimum and maximum) for both temperature and precipitation and a variable describing the annual rainfall variation as a measure for seasonality [36].…”
Section: Geological Surveymentioning
confidence: 99%
“…Climate change affects the geographical distribution of many sand fly species [65,66]. As a consequence, the geographical distribution of sand flies has expanded towards Northern Europe during the last decade.…”
Section: Sandflies As Tosv Vectorsmentioning
confidence: 99%